Significance of pancreatic duodenal homeobox-1 (PDX-1) genetic polymorphism in insulin secretion in Japanese patients with type 2 diabetes. Issue 5 (8th September 2022) - Okura, Tsuyoshi; Nakamura, Risa; Ito, Yuichi; Kitao, Sonoko; Anno, Mari; Endo, Satomi; Taneda, Natsuka; Matsumoto, Kazuhisa; Shoji, Kyoko; Okura, Hiroko; Matsuzawa, Kazuhiko; Izawa, Shoichiro; et al.
Abstract : Introduction: Pancreatic and duodenal homeobox factor-1 ( PDX-1 ) is an imperative gene for insulin secretion in maturity-onset diabetes of the young 4. PDX-1 gene polymorphism was associated with lower first-phase insulin secretion in a genome-wide association study of intravenous glucose tolerance test. It was not associated with type 2 diabetes risk and insulin secretion in a genome-wide oral glucose tolerance test study. However, there have been no reports of overt type 2 diabetes and insulin resistance evaluation using a glucose clamp. We investigated PDX-1 polymorphism, insulin secretion, and insulin resistance in overt type 2 diabetes. Research design and methods: We performed a meal tolerance test (MTT) and hyperinsulinemic–euglycemic clamping on 63 Japanese subjects, 30 with type 2 diabetes and 33 non-diabetic. We analyzed the rs1124607 PDX-1 gene polymorphism and defined A/C and C/C as the high-risk group and A/A as the low-risk group. Results: HOMA-beta (homeostatic model assessment beta-cell function) was significantly lower in the high-risk group than in the low-risk group for all subjects (72.9±54.2% vs 107.0±63.5%, p<0.05). Glucose levels and glucose area under the curve (AUC) were not significantly different between both the risk groups. The insulin levels at 60 and 120 min and the insulin AUC after MTT were remarkably lower in the high-risk group than those in the low-risk group for all subjects (AUC 75.7±36.7 vs 112.7±59.5, p<0.05). High-risk subjects with type 2 diabetes had significantly lower insulin levels at 30 and 60 min and insulin AUC than low-risk subjects. Non-diabetic high-risk subjects depicted significantly lower insulin levels at 120 and 180 min. There were negligible differences in insulin resistance between the risk groups. Conclusions: These results suggest that the PDX-1 genetic polymorphism is crucial for insulin secretion in Japanese patients with type 2 diabetes.